Corruption and Technology-Induced Private Sector Development - Ruhashyankiko, Jean-Francois (IMF Working Papers; Working Paper ;, 2006)
This paper asks whether corruption might be the outcome of a lack of outside options for public officials or civil servants. We propose an occupational choice model embedded in an agency framework to address the issue. We show that technology-induced private sector expansion leads to a decline in publicly supplied corruption as it provides outside options to public officials who might otherwise engage in corruption. We provide empirical evidence that strongly shows that technology-induced private sector development is associated with a decline in aggregate corruption. This suggests that the decline in publicly supplied corruption outweighs the potential increase in privately supplied corruption that could result from private sector expansion.